Types of Synchronous Corpus and Their Significance (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
A synchronous corpus is a collection of texts or conversations that have been recorded or transcribed in real-time. There are several types of synchronous corpora, each serving a specific purpose in linguistic research and language study. Some common types of synchronous corpora include spoken language corpora, chat corpora, and text messaging corpora. Synchronous corpora play a crucial role in linguistic research by providing researchers with real-life examples of language use in various contexts. They offer a rich source of data for studying language variation, language change, and the impact of technology on language use. By analyzing synchronous corpora, researchers can gain a deeper understanding of how language is used in everyday communication and how it evolves over time.